1999
DOI: 10.1108/01425459910273134
|View full text |Cite
|
Sign up to set email alerts
|

Investment in management training and development by small businesses

Abstract: The topic of management training and development (MTD) in small businesses is relatively under‐researched, and an increased understanding of the factors influencing the purchase of MTD by small businesses is needed. Therefore, a survey of 551 small businesses in the Midlands region of the UK sought to: identify influences on MTD investment and preferred MTD activities; and establish whether small businesses perceive a link between investment in MTD and business success. Interviews were also conducted with 12 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 15 publications
6
48
0
1
Order By: Relevance
“…Training in SMEs has been described as informal and on-the-job, with little or no provision for management development (Loan-Clarke et al 1999;Marlow and Patton 1993;Storey 1994). …”
Section: Training and Performance Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Training in SMEs has been described as informal and on-the-job, with little or no provision for management development (Loan-Clarke et al 1999;Marlow and Patton 1993;Storey 1994). …”
Section: Training and Performance Appraisalmentioning
confidence: 99%
“…It is increasingly recognised that small and medium enterprises (SMEs) are complex, varied, and influenced by a range of factors (Loan-Clarke, Boocock, Smith, and Whittaker 1999;Wagar 1998) and thus cannot be depicted by static models (Reid and Adams 2001;Baron and Kreps 1999). SMEs encompass firms of various sizes with varying degrees of complexity in management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Loan-Clarke et al mentioned that the topic of management training and development (MTD) in small enterprises is relatively under-researched. In their study, the results showed that the investments that were made on MTD were significantly influenced by the organisational characteristics of ownership, size, number of managers, and family management, but 85% of the studied sample considered investment in MTD to be linked to business success [10]. Moreover, Harel and Tzafrir also found that training practices affected perceived organizational performance in a way that is statistically significant [11].…”
Section: Educational Trainings For the Randd Institutions: State Of Thementioning
confidence: 95%
“…[35], there are few reasons for a company to invest in training without assessing the results. This is specially true if one takes into account the fact that there is very little empirical evidence that supports what is intuitively postulated, ie that the training enhances the performance of the company [36; 37; 38; 39] and hence has an impact on economic development [40]. However, some researchers have identified a positive relation between training and performance [20; 31; 41; 42].…”
Section: Training Evaluationmentioning
confidence: 95%